Pengelolaan Dana Desa dalam Upaya Pembangunan Pedesaan di Kecamatan Donorojo Kabupaten Jepara - Zaka Nurfahruddin; Edy Yusuf Agung Gunanto (Diponegoro Journal of Economics, 2020)
This study aims to describe how the management of the Village Fund (VF) and Village Fund Allocation (VFA) carried out in Donorojo Subdistrict, Jepara Regency whether it is in accordance with applicable procedures, the role of the Village Fund and the Village Fund Allocation in rural development, as well as the factors influence the implementation of the Village Fund (VF) and Village Fund Allocation (VFA) policies. This study uses a qualitative descriptive approach, with the aim of being able to describe or give an idea of the object under study. The object of this study is the Village Head, Village Officials, the District Head, and Other Village Institutions as resource persons or informants. Data analysis methods used are data reduction, data presentation, and drawing conclusions. The results of this study indicate that the management of the Village Fund and the Village Fund Allocation in Donorojo Subdistrict have been quite good, although the disbursement of funds and accountability reporting has been delayed. In managing VF and VFA, community participation is quite good. VF and VFA also had a good influence on development in Donorojo District. In addition, there are factors that influence the implementation of the Village Fund and Village Fund Allocation policies, including communication, resources, pelasana attitude, bureaucratic structure and the environment.